Internal information of the company and the position of Iraqi legislation and comparative legislation to prohibit disclosure - الساعدي, هيفاء مزهر (Journal of Legal Sciences, 2020)
Few people are familiar with the company 's internal information, through the job center they hold at that company, or perhaps through relationships with people familiar with it.    If the sale or purchase of shares is based on that information, which was the reason for the insider's job or his relations with those familiar with it, which would lead to the collection of profits at the expense of people who do not have access to that information, all of which would violate justice in the financial market. The lack of access to that information was not due to the lack of effort by him to know the extent of this information on the prices of stocks, or lack of experience in the financial market, but due to the job and the position of insider or his relationship with insiders on internal information, which undermines confidence In the securities market Financial, and this is reflected in turn to the reluctance of many to invest in stocks people, and confusion in economic growth..